EFFORTS TO OPTIMIZE INTERNET USE IN ENGLISH LANGUAGE LEARNING - Andayani, Endang Sri (Universitas Indraprasta PGRI, 2024)
Internet in learning English has become increasingly significant along with technological developments and the need for high language skills in the digital era. This research aims to identify effective strategies and methods in optimizing the use of the internet as a tool in learning English at SMP PGRI 1 Bekasi. The research method used is qualitative with a descriptive approach. The research results show that the use of the internet in learning English at SMP PGRI 1 Bekasi significantly improves the quality and effectiveness of learning. The implementation of video and audio from digital platforms, e-books and online articles enriches students' learning experiences, while e-learning platforms make class management and interaction between teachers and students easier. Interactive applications and educational games increase student engagement, and the use of blogs, online forums, and video conferencing tools strengthen students' writing and speaking skills. Additionally, social media and writing platforms provide additional access and collaboration opportunities, supporting more dynamic and enjoyable learning.